The Position of Women in the Islamic Legal Inheritance System in Indonesia - Muhammadong (Yayasan Cinta Negara, 2025)
This study examines the position of women in the Islamic legal inheritance system as applied in Indonesia, a country where Islamic law, national law, and local customs coexist within a pluralistic legal framework. The research aims to analyze the extent to which Islamic inheritance law, particularly as codified in the Compilation of Islamic Law (Kompilasi Hukum Islam), recognizes and protects women's rights to inheritance, while also addressing the social and cultural challenges that affect its implementation. Although Islamic law grants women specific shares in inheritance such as one-half or one-third depending on their relationship to the deceased its practical enforcement is often hindered by patriarchal interpretations, customary practices (adat), and limited legal awareness among the Muslim population. Using a normative-juridical method, this study evaluates primary legal sources, including the Qur’an, Hadith, the Compilation of Islamic Law, and relevant court decisions. The research also explores the tension between religious doctrine and societal norms that tend to marginalize women from their rightful inheritance. Findings suggest that while the Islamic legal system in Indonesia formally acknowledges women's inheritance rights, cultural resistance and legal ambiguities frequently undermine their realization. Furthermore, there remains a significant gap between legal theory and practice, especially in rural communities. The study recommends strengthening legal education, judicial consistency, and public awareness to ensure that women's inheritance rights are upheld in accordance with Islamic principles of justice and equity. This research contributes to the broader discourse on gender justice within Islamic jurisprudence and the ongoing efforts to harmonize religious law with human rights standards in Indonesia